Mechanisms To Strengthen The Tourism Sector and Boost its Development Role in Algeria - عاشوري إبراهيم; بن موسى محمد (Finance and Business Economies Review, 2021)
Through this research we will aim to diagnose the tourist momentum in Algeria , as well as proposing a set of mechanisms that will achieve the upgrading of the role assigned to the tourism sector in Algeria, especially in light of high cries of this stage of the economic trend calling for the economic diversification of Algeria's income and not to rely on depleted resources (fossil energy). The research found that tourism investment in Algeria is facing several obstacles. Although Algeria has huge tourist qualifications, it is classified as the weakest tourist destination, therefore, it is necessary to plan for comprehensive development, through directing and focusing efforts towards activating and promoting the tourism sector.